Les conditions favorables à la collaboration entre enseignantes et orthopédagogues en contexte d’implantation du modèle de réponse à l’intervention (RàI) au premier cycle du primaire - Boily, Élisabeth; Ouellet, Chantal; Thériault, Pascale (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
The need to establish real collaboration between teachers and remedial teachers is highlighted by several studies and ministerial documents. Despite the potential benefits of this collaboration, several obstacles hinder the implementation of these collaborative practices. This multi-case study, carried out as part of doctoral studies, aims to document the collaboration between teachers and remedial teachers in the context of the implementation of the RtI model in elementary school. To do this, three dyads, each composed of a teacher and a remedial teacher, were studied in depth based on interviews, direct observation, documentary analysis and a logbook. The results highlight favorable conditions for the establishment of a real collaboration between teachers and remedial teachers, as well as the presence of a parity imbalance within certain dyads. These results reiterate the importance of further research on collaboration between teachers and remedial teachers to further guide practitioners, managers and university trainers.